Do High Interest Rates Defend Currencies during Speculative Attacks? - Kraay, Aart 1995- (The World Bank, 2000)
January 2000 - No - there is no systematic association between interest rates and the outcome of speculative attacks. Drawing on evidence from a large sample of speculative attacks in industrial and developing countries, Kraay argues that high interest rates do not defend currencies against speculative attacks. In fact, there is a striking lack of any systematic association between interest rates and the outcome of speculative attacks. The lack of clear empirical evidence on the effects of high interest rates during speculative attacks mirrors the theoretical ambiguities on this issue. This paper - a product of Macroeconomics and Growth, Development Research Group - is part of a larger effort in the group to study the causes and consequences of financial crises. The author may be contacted at akraay@worldbank.org